âKampungâ as a Formal and Informal Integration Model (Case Study: Kampung Pahandut, Central Kalimantan Province, Indonesia) - Hamidah, Noor; Rijanta, R; Setiawan, Bakti; Marfai, Muh. Aris (Universitas Muhammadiyah Surakarta, 2017)
Kampung is a mixed formal and informal settlements which has a long history. Kampung has always been occupied by millions of in Indonesia. Kampung shows its capacity to integrate formal and informal activities both within the kampung itself and activities at city level. This research try to explore Kampung Pahandut, Central Kalimantan Province, Indonesia as a case study of embryo settlement close to the river. The objective of this research is to describe of formal and informal in formal and informal activities within Kampung Pahandut. This research attempt to study the pattern and the forms of socio-economic integration of the community. This research applies mixed method (qualitative and quantitative) through field observation as a step to find the integration of formal and informal activity in Kampung. Data collection is primarily to record both social and economic activities since field observation records physical appearances of infrastructure. In addition, this Kampung research was also conducted through in-depth interview to explore information from the selected resource persons. This research approves that Kampung, in the case of Kampung Pahandut, is not separated both physical and social from the city of Palangka Raya. It is reveal that internal social activity ofÂ Kampung are able to maintain âgotong-royongâ and external social activity showed by âgreen kampungâ. Kampung Pahandut is a part of the Palangka Raya city government by kampung improvement program. It means integration through physical and social activities shows that kampungs are not isolation settlements. Kampung has its significant contributions to the social and physical of the Palangka Raya city. It is as proven by formal and informal activities of Kampung Pahandut which is found to be fully integrated to the city of Palangka Raya.